A 0D stationary model for the evaluation of the degree of detachment on the divertor plates. (2nd November 2016) - Siccinio, M; Fable, E; Lackner, K; Scarabosio, A; Wenninger, R P; Zohm, H
Abstract: A 0D analytical stationary model to estimate the degree of detachment on the divertor plates is derived, starting from previous works of Igitkhanov (Igitkhanov et al 1994 21st EPS (Montpellier) ECA v.18B, 1995 22th EPS (Bournemouth) ECA v.19C, Igitkhanov 2014 KIT Sci. Rep . 7661). It accounts for heat convection, conduction, impurity radiation and contains a simplified balance for the neutrals. The upstream particle flux Γ u p (or, alternatively, the density upstream n up ), the heat flux in the scrape-off layer (SOL) q up and the impurity concentrations are required as input, whereas the temperatures at the plate and at the separatrix are not fixed a priori . The routine has been mainly developed for system codes, or more in general for scopy studies in the framework of the preliminary design phase for the reactor DEMO, its simplicity being therefore justified by the purpose of keeping the calculation times as low as possible. A calibration against a more detailed 1D routine (Kallenbach et al 2016 Plasma Phys. Control. Fusion 58 045013) has been performed, finding a reasonable agreement. Furthermore, a coupling of the model with the 1.5D transport code ASTRA (Pereverzev 1991 IPP Report 5/42, Fable et al 2013 Plasma Phys. Control. Fusion 55 124028) to illustrate its possible usage is also presented.